2018
DOI: 10.1016/j.bbamcr.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Rab7a modulates ER stress and ER morphology

Abstract: The Endoplasmic Reticulum (ER) is a membranous organelle with diverse structural and functional domains. Peripheral ER includes interconnected tubules, and dense tubular arrays called "ER matrices" together with bona fide flat cisternae. Transitions between these states are regulated by membrane-associated proteins and cytosolic factors. Recently, the small GTPases Rab10 and Rab18 were reported to control ER shape by regulating ER dynamics and fusion. Here, we present evidence that another Rab protein, Rab7a, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…YIF1A recycles between the ER and the Golgi with a major ERGIC localization, maintaining homeostasis of the early secretory pathway (Yoshida et al, 2008). Rab7a modulates ER morphology by controlling ER stress responses (Mateus et al, 2018). Thus, these CoV-2 interactions may be crucial to controlling ER morphology and homeostasis, limiting induction of ER stress and apoptosis.…”
Section: Er Homeostasismentioning
confidence: 99%
“…YIF1A recycles between the ER and the Golgi with a major ERGIC localization, maintaining homeostasis of the early secretory pathway (Yoshida et al, 2008). Rab7a modulates ER morphology by controlling ER stress responses (Mateus et al, 2018). Thus, these CoV-2 interactions may be crucial to controlling ER morphology and homeostasis, limiting induction of ER stress and apoptosis.…”
Section: Er Homeostasismentioning
confidence: 99%
“…Some of the apical vesicular structures containing ntChx were also positive for Rab7 (Figure 2c), a protein involved in early-to-late endosome maturation, modulation of ER homeostasis and stress, and endosome-to-TGN trafficking. [23][24][25] Similar to EEA1, Rab7/ntChx co-localizations were restricted to the apical region of enterocytes, with large Rab7 + vesicles being present that were consistent with lysosomal structure but which did not contain ntChx.…”
Section: In Vivo A→b Transcytosis Across Rat Intestinal Epitheliummentioning
confidence: 89%
“…A previous study showed that RAB7A gene expression in the postmortem brain was up-regulated in patients with depression who died by suicide [34]. Recently, RAB7A was demonstrated to modulate endoplasmic reticulum stress [35], which is associated with mood disorders [36,37]. Other functions of RAB7A include growth-factormediated cell signalling and lipid metabolism [38], which are also proposed mechanisms involved in the pathophysiology of mood disorders [39,40].…”
Section: Discussionmentioning
confidence: 99%